Barras bravas, barrismo social y convivencia en el fútbol: un análisis de la producción bibliográfica en Colombia entre los años 2000 y 2023 (2023)
This compilation monograph aims to analyze bibliographic documents in Colombia through specialized analytical summaries regarding hooligan groups, approaching the categories of social hooliganism and football coexistence. This allows for the identification of different objectives, methodologies, and perspectives addressed by authors between the years 2000 and 2023.